RESPON SAREKAT ISLAM TERHADAP KEBIJAKAN PENDIDIKAN PEMERINTAH KOLONIAL BELANDA (1905-1933) - Dwi Lestari (Progam Studi Sejarah Peradaban Islam (SPI), Fakultas Ushuluddin Adab dan Humaniora, Universitas Islam Negeri Prof. K.H. Saifuddin Zuhri Purwokerto, 2022)
In the early 20th century, education experienced many polemics due to the policies of the Goeroe Ordinance and the Illegal Schools Ordinance. In 1922, for the first time the Goeroe Ordinance met resistance from the Sarekat Islam. And then this organization became a pillar of resistance for the people. This study uses the theory of